Experimental Study of Rheological Behavior and Steam Gasification of Coal Bio-Oil Slurry - Wang, Yongwei; Wang, Ze; Li, Songgeng; Lin, Weigang; Song, Wenli (Energy & fuels, 2010)
Coal bio-oil slurries (CBS) with different coal concentrations are prepared by mixing Yangquan anthracite and biomass fast pyrolysis oil. The rheological properties of CBS are examined. The result shows that the solid concentration of CBS can reach 42% without any additives. The rheological behavior of the prepared CBS can be described by the Bingham plastic fluid model. Its apparent viscosity decreases with increasing shear rates, and the yield stress increases with increasing solid concentrations. The CBS keeps its static stability for 3−4 days with no formation of soft sediment. The steam gasification experiment of CBS is carried out on a lab-scale apparatus with a fixed bed reactor. The effects of reaction temperature and steam to carbon ratio (S/C) on the gas yield and component distribution are investigated. The result shows that the yield of H2 and CO increases with temperature and that the ratio of H2/CO decreases with temperature and increases with S/C. The higher heating value of the gas product is about 12 MJ/Nm3.